Modeling evolutionary games in populations with demographic structure. (7th September 2015) - Li, Xiang-Yi; Giaimo, Stefano; Baudisch, Annette; Traulsen, Arne
Abstract: Classic life history models are often based on optimization algorithms, focusing on the adaptation of survival and reproduction to the environment, while neglecting frequency dependent interactions in the population. Evolutionary game theory, on the other hand, studies frequency dependent strategy interactions, but usually omits life history and the demographic structure of the population. Here we show how an integration of both aspects can substantially alter the underlying evolutionary dynamics. We study the replicator dynamics of strategy interactions in life stage structured populations. Individuals have two basic strategic behaviours, interacting in pairwise games. A player may condition behaviour on the life stage of its own, or that of the opponent, or the matching of life stages between both players. A strategy is thus defined as the set of rules that determines a player׳s life stage dependent behaviours. We show that the diversity of life stage structures and life stage dependent strategies can promote each other, and the stable frequency of basic strategic behaviours can deviate from game equilibrium in populations with life stage structures. Abstract : Graphical abstract: Abstract : Highlights: We define a strategy as a set of life stage dependent behaviours in a game. Behaviours can be conditioned on the life stage of one of the two players. Behaviours can be conditioned on the matching of life stages between the two players. We use the replicator dynamics to study the evolution of life stage dependent strategies. The equilibrium with life stage dependence can deviate from the game equilibrium.